(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Candida spp, which causes skin and mucous membrane infection, is resistant to many antifungal drugs. This study was conducted to determine the sensitivity of Candida spp in patients treated at Quy Hoa National Leprosy Dermatology Hospital to find the most effective antifungal drugs. Study subjects and methods: The study was conducted in the laboratory with a descriptive research design. Results: C. albicans was sensitive to Amphotericin B, Econazole and Nystatin at high rates of 73.33%, 73.33% and 60.00%, respectively. C. tropicalis was susceptible to Amphotericin B at the rate of 75.00%, and resistant to 5-fluorocytosine, Ketoconazole and Miconazole at the resistance rate of 75.0%, 50.0%. C. glabrata was sensitive to many Miconazole-based antifungal drugs at 100%, to Amphotericin B at 75%, and to Fluconazole and Nystatin, but resistant to Ketoconazole, 5-fluorocytosine and Itraconazole at 50%. C. parapsilosis was susceptible to many antifungal drugs such as Clotrimazole, Itraconazole, Fluconazole, Nystatin and Amphotericin B at the rates of 100%. C. parapsilosis was resistant to 5-fluorocytosine and Miconazole at 50.0%. Conclusions: Most of the Candida spp, such as C. albicans, C. tropicalis, C. glabrata, C. glabrata were susceptible to Amphotericin B with susceptibility rates ranging from 75.0% to 100.0%.